The in vivo properties of STX243: a potent angiogenesis inhibitor in breast cancer - Parsons, M F C (Nature Publishing Group, 2008)
The steroidal-based drug 2-ethyloestradiol-3,17-O,O-bis-sulphamate (STX243) has been developed as a potent antiangiogenic and antitumour compound. The objective of this study was to ascertain whether STX243 is more active in vivo than the clinically relevant drug 2-methoxyoestradiol (2-MeOE2) and the structurally similar compound 2-MeOE2-3,17-O,O-bis-sulphamate (STX140). The tumour growth inhibition efficacy, antiangiogenic potential and pharmacokinetics of STX243 were examined using four in vivo models. Both STX243 and STX140 were capable of retarding the growth of MDA-MB-231 xenograft tumours (72 and 63%, respectively), whereas no inhibition was observed for animals treated with 2-MeOE2. Further tumour inhibition studies showed that STX243 was also active against MCF-7 paclitaxel-resistant tumours. Using a Matrigel plug-based model, in vivo angiogenesis was restricted with STX243 and STX140 (50 and 72%, respectively, using a 10 mg kg(−1) oral dose), thereby showing the antiangiogenic activity of both compounds. The pharmacokinetics of STX243 were examined at two different doses using adult female rats. The compound was orally bioavailable (31% after a single 10 mg kg(−1) dose) and resistant to metabolism. These results show that STX243 is a potent in vivo drug and could be clinically effective at treating a number of oncological conditions.